Mental health disorders among children with special health needs: A population-based cohort study using linked administrative data from Manitoba, Canada - Jennifer E. Enns; Caroline Reid-Westoby; Gilles R. Detillieux; Marni Brownell; Nathan C. Nickel; Anne Gadermann; Astrid Guttmann; Teresa Bennett; Eric Duku; Barry Forer; Monique Gagné Petteni; Katholiki Georgiades; et al. (PLoS ONE, 2025)
Objective An estimated 15–22% of Canadian kindergarten-age children have a special health need (SHN), defined as a clinical diagnosis, a functional need requiring special accommodation at school, or a health condition leading to increased needs. Children with SHN may be more likely to experience mental health disorders than their peers without SHN, placing them at risk for further health and academic challenges. Our objective was to determine the odds of children with SHN identified in kindergarten being diagnosed with a mental health disorder by age 16. Methods In this retrospective cohort study using population-based, linked administrative data, we identified children with SHN born 1995–2020 in Manitoba, Canada, and enrolled in kindergarten from 2006–2011. The SHN designation is derived from the Early Development Instrument. We measured prevalence of common childhood mental health disorders (ADHD, mood/anxiety disorders, conduct disorders) in children with SHN to age 16. Using binary logistic regressions, we calculated crude odds ratios (OR) for children with vs. without SHN being diagnosed with a mental health disorder, then adjusted for age, sex, and neighbourhood-level income. Results Among 42,766 children, 13.8% had a SHN designation in kindergarten. Among these, 41.0% were diagnosed with a mental health disorder by age 16. The odds of a mental health diagnosis by SHN category were: special needs designation in kindergarten (OR 1.75, 95%CI 1.53–2.01); learning impairment (OR 1.61, 95%CI 1.39–1.86); behavioural impairment (OR 3.27, 95%CI 2.87–3.72); and emotional impairment (OR 2.01, 95%CI 1.75–2.32). Children with SHN (vs. none) had higher odds of a mental health disorder if they had 1 + impairment (OR 1.67, 95%CI 1.50–1.85). Adjusting for sociodemographic characteristics did not change the estimates. Conclusions The study highlights important kindergarten predictors of future mental health disorders in children, which should be used to inform preventive and supportive strategies for children with SHN and help generate wider mental health supports in schools.